Sistemática das espécies brasileiras oceladas de Trichorhina Budde-Lund, 1908 (Crustacea, Isopoda Oniscidea) - Kury, Leila Aparecida Souza (1991)
An emended diagnosis for the Platyarthridae Verhoeff, 1949 is herein presented, as well as a key to its genera and an overview of their geographic distribution. A similar account is sketched for Trichorhina Budde-Lund, 1908, and a check list is organized for the species of the genus, constituted by 49 extant and one fossil species. Graphics depicting noduli laterales are used for the first time in the characterization of species within the family. SEM micrographs are employed to check some diagnostic features for the genus. Attention is called for the need of a replacement name for trichorhina squamata (Verhoeff, 1933), junior secondary homonym of Trichorhina squamata Verhoeff, 1926. Trichorhina yucatanensis Hulaik, 1960 is newly considered a junior subjective synonym of Porcellio pearsei Creaser, 1938, currently included in Trichorhina. Of the three species of ocel lated Trichorhina hitherto recorded from Brazi 1, one – Trichorhina barbouri (Name, 1926), originally described from the Panama – is due to a misidentification. The other two – Trichorhina tomentosa (Budde-Lund, 1908) and Trichorhina heterophthalma Lemos de Castro, 1964 – are confirmed, and eleven hitherto undescribed species of Trichorhina (T. spp A to L) are herein characterized. A key to the 13 species of ocellated Trichorhina recorded from Brazil is given, and their geographic distribution is illustrated in a map.